Osthole inhibits proliferation and induces apoptosis in BV-2 microglia cells in kainic acid-induced epilepsy via modulating PI3K/AKt/mTOR signalling way - Meng Du (Taylor & Francis Group, 2019)
Context: Osthole is a natural coumarin compound most frequently extracted from plants of the Apiaceae family such as Cnidium monnieri (L.) Cusson, Angelica pubescens Maxin.f., and Peucedanum ostruthium (L.). Osthole is considered to have potential therapeutic applications for the treatment of diseases including epilepsy. However, the mechanism of osthole induced-apoptosis in BV-2 microglia cells is not yet clear. Objective: To investigate the molecular mechanisms underlying the effect of osthole on PI3K/AKt/mTOR expression in kainic acid (KA)-activated BV-2 microglia cells. Materials and methods: Optimal culture concentration and time of osthole were investigated by MTT assay. The concentration of osthole was tested from 10 to 400 μM and the culture time was tested from 2 to 72 h. Ultrastructure difference among control, KA and osthole group was analyzed under transmission electron microscope. The mRNA expression of PI3K/AKt/mTOR was investigated using reverse transcription (RT)-PCR and the protein expression was investigated using western blotting and immunofluorescence assay. Apoptosis rate of BV-2 cells between each group was measured by flow cytometry. Results: IC50 for cell viability of BV-2 cells by osthole was 157.7 µM. Treated with osthole (140 µM) for 24 h significantly increased the inhibition rate. Pretreatment with osthole inhibited the KA-induced PI3K/AKt/mTOR mRNA and protein expression. The results of flow cytometry analysis showed that the apoptotic rate of osthole group was obviously higher than KA group. Conclusions: Date showed that osthole may be useful in the treatment of epilepsy and other neurodegenerative diseases that are characterized by over expression of PI3K/Akt/mTOR.